2020
DOI: 10.1007/s11356-020-09053-z
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine removal using Elaeis guineensis activated carbon: adsorption and RSM studies

Abstract: The palm (Elaeis guineensis), known as dendê, is an important oleaginous Brazilian plant with a high performance of oil production. In this work, a 2 3 full experimental design was performed and the response surface method (RSM) was used to indicate the optimum parameter of caffeine adsorption on Elaeis guineensis endocarp activated carbon, since the endocarp is the main by-product from dendê oil production. It was set the adsorbent point of zero charge (pH pzc), and the material was characterized by Fourier t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 67 publications
3
23
0
Order By: Relevance
“…It exhibits the Freundlich isotherm characteristics at low adsorbate concentrations and the Langmuir isotherm characteristics with monolayer capacity at high concentrations. 70 When Table 2 is examined, it is concluded that most of the adsorption studies are in agreement with the Langmuir and Freundlich isotherm models.…”
Section: Determination Of Equilibrium Adsorption Isothermsmentioning
confidence: 79%
See 1 more Smart Citation
“…It exhibits the Freundlich isotherm characteristics at low adsorbate concentrations and the Langmuir isotherm characteristics with monolayer capacity at high concentrations. 70 When Table 2 is examined, it is concluded that most of the adsorption studies are in agreement with the Langmuir and Freundlich isotherm models.…”
Section: Determination Of Equilibrium Adsorption Isothermsmentioning
confidence: 79%
“…It exhibits the Freundlich isotherm characteristics at low adsorbate concentrations and the Langmuir isotherm characteristics with monolayer capacity at high concentrations. 70 …”
Section: Caffeine Adsorption and Affecting Parametersmentioning
confidence: 99%
“…With the intention of assess the effect of different aqueous mediums on the caffeine removal, adsorption experiments were achieved using lagoon (Mundaú Lagoon, Maceió/AL, Brazil), tap and mineral water. The initial caffeine concentration was 75 mg.L -1 , 50 mg of CLAC, 30° C and 40 min contact time were used for the tests [36].…”
Section: Ionic Strength and Influence Of Aqueous Matricesmentioning
confidence: 99%
“…Regarding pH, acidic pHs in the range 2-5 tend to yield the best results, such as produced as follows: at pH 2, a maximum adsorption capacity of 13 mg/g for the activated carbon obtained from Elaeis guineensis (palm oil) [93]; at pH 3, a Q max of 212.3 mg/g for biomass-derived activated carbons (dende coco and babassu coco) [94]; at pH 4, a Q max of 916.7 mg/g for grape stalk activated carbon [92]; and at pH 5, a Q max of 500 mg/g for pine activated carbon with K 2 CO 3 [91]. For pH values between 6.3 and 7.7, a Q max of 30.3 to 270 mg/g has been reported, being the case of activated carbons obtained from residues of Acacia mangium wood, pineapple plant leaves, Eragrostis plana, and peach stones [51,54,95,96].…”
Section: Organic Adsorbentsmentioning
confidence: 99%